2019
DOI: 10.1093/aje/kwz149
|View full text |Cite
|
Sign up to set email alerts
|

Public Transportation Use and Cognitive Function in Older Age: A Quasiexperimental Evaluation of the Free Bus Pass Policy in the United Kingdom

Abstract: In this quasiexperimental study, we examined whether the introduction of an age-friendly transportation policy—free bus passes for older adults—increased public transport use and in turn affected cognitive function among older people in England. Data came from 7 waves (2002–2014) of the English Longitudinal Study of Ageing (n = 17,953), which measured total cognitive function, memory, executive function, and processing speed before and after the bus pass was introduced in 2006. The analytical strategy was an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…This was also a concern in countries like China [15] and South Korea [5]. In countries like the United Kingdom and Hong Kong, free passes and minimal cost rate for older adults have been shown to be effective in boosting mobility and transport use [16] [17]. There was transportation concession fare for older adults in Malaysia as well.…”
Section: Discussionmentioning
confidence: 99%
“…This was also a concern in countries like China [15] and South Korea [5]. In countries like the United Kingdom and Hong Kong, free passes and minimal cost rate for older adults have been shown to be effective in boosting mobility and transport use [16] [17]. There was transportation concession fare for older adults in Malaysia as well.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study of UK reported that transportation policies (free bus travel) may increase the elderly’s cognitive functions through participation in volunteering activities and contact with older people’s adult children and friends [ 76 ]. Therefore, social policies for the retired and homemakers are needed to reduce the risks of cognitive impairment such as lifelong learning, volunteer work, and participation in social and leisure activities either at home or in community centers [ 43 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The g-factor at wave 7 ranged between − 4.22 and 3.36. This approach has previously been used to examine cognitive function assessed by several tasks, in ELSA [40][41][42] and in other cohort studies [43][44][45].…”
Section: Cognitive Functionmentioning
confidence: 99%